2020
DOI: 10.3389/fmicb.2020.539921
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Sediment Microbial Communities Are Not Resilient to Disturbance From Agricultural Land Runoff

Abstract: Microorganisms are critically important for the function of surface water ecosystems but are frequently subjected to anthropogenic disturbances at either acute (pulse) or long-term (press) scales. Response and recovery of microbial community composition and function following pulse disturbance is well-studied in controlled, laboratory scale experiments but is less well-understood in natural environments undergoing continual press disturbance. The objectives of this study were to determine the drivers of sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
0
19
0
1
Order By: Relevance
“…Freshwater ecosystems are altered by both natural and anthropogenic pulse disturbances that alter community composition and functioning for varying periods of time. Previously, our laboratory found that long-term press disturbance from manure fertilization runoff resulted in sediment microbial communities that reached a new steady state within 5 months post-disturbance (Beattie et al, 2020). However, we were not able to capture the full dynamics of manure F I G U R E 2 Relative abundance of amplicon sequence variants (ASVs) mapped to 'highly abundant' genera, or those with a relative abundance of at least 0.25% across all samples post-experimental setup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Freshwater ecosystems are altered by both natural and anthropogenic pulse disturbances that alter community composition and functioning for varying periods of time. Previously, our laboratory found that long-term press disturbance from manure fertilization runoff resulted in sediment microbial communities that reached a new steady state within 5 months post-disturbance (Beattie et al, 2020). However, we were not able to capture the full dynamics of manure F I G U R E 2 Relative abundance of amplicon sequence variants (ASVs) mapped to 'highly abundant' genera, or those with a relative abundance of at least 0.25% across all samples post-experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…Two mesocosm replicates from each treatment on Days 1, 3, 7, 14 and 28 were also sequenced. Sequencing parameters and quality control have been described fully elsewhere (Beattie et al, 2020). Briefly, samples were sequenced using the Illumina MiSeq Platform at the University of Wisconsin Biotechnology Center (Madison, Wisconsin, USA) using 16S rRNA primers for the V3‐V4 hypervariable region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic ecosystems support a wide variety of habitats that may be altered by anthropogenic contamination contributing to the decline of water quality worldwide. Water quality is a significant concern, especially in areas of intensive livestock farming (Burkholder et al, 2007;Li et al, 2015;Jacobs et al, 2019;Beattie et al, 2020). Runoff from agricultural fields has been shown to contain elevated levels of livestock contaminants including ammonia, nitrogen, and ARB (Sobsey et al, 2006;Beattie et al, 2018;Le et al, 2018;Tang et al, 2020).…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
“…Our results showed that after decades of biogeochemical cycles, the concentrations of TOC, Br and Cl turned out to be main factors affecting the microbial communities in sediments from the degraded stage (Figure 2). Another possible reason for the "records" might be the weak resilience of microbial communities under anthropogenic disturbance (Beattie et al, 2020). Chen et al reported geological evidence for the fragility of Hongfeng Reservoir and another karst reservoir that can hardly recover from pollution even after a long period (Chen et al, 2020).…”
Section: Historical Water Quality Can Be Recorded In the Sediment And Reflected By Microbial Communitymentioning
confidence: 99%